Under Graduate Students’ Perception Towards Online Course: Nptel - et. al., Dr.A.Jeyalakshmi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nowadays students are willing to take online courses to improve their skill set. Their course curriculum is not sufficient to face the competitive environment. With digital learning on the rise, the NPTEL will offer more flexible options to students for their education. The present study was conducted to know the perception of the undergraduate students towards the online NPTEL courses. Chi square test was used to identify the association b etween the year of study and the issues faced by them.